Thought experiments in the Jefferson-Turing controversy: A Kuhnian perspective - García, Pío (THEORIA. An International Journal for Theory, History and Foundations of Science, 2024)
In this article we propose an analysis of the controversy between Geoffrey Jefferson and Alan Turing in terms of a Kuhnian account of thought experiments. In this account, the main task is not to evaluate intuitions or (only) to rearrange concepts. Instead, we propose that the main task is to construct scenarios by proposing relevant experiences in which shared assumptions and conflicting lines of inquiry can be made explicit. From this perspective, we can understand the arguments and assumptions in the Jefferson-Turing thinking machine controversy.